Let f(x) = -5x - 4 and g(x) = 6x - 7. Find f(x) + g(x) A. -11x 3 B. x 3 C. -11x - 11 D. x - 11

Let f(x) = -5x - 4 and g(x) = 6x - 7. f(x) + g(x) = -5x - 4 + 6x - 7 = x - 11

s

Question

Asked 11/30/2014 5:27:37 PM

Updated 11/30/2014 7:00:52 PM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Edited by andrewpallarca [11/30/2014 7:00:51 PM], Confirmed by andrewpallarca [11/30/2014 7:00:52 PM]

Rating

There are no new answers.

34,458,229

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 723 [Total 6596] Ratings 14 Comments 583 Invitations 0 Offline

There are no comments.